Fungal deterioration of anti-corrosive coating: assessment by electrochemical techniques and scanning electron microscopy - Roselli, Sol Natacha (2020)
Microorganisms grow on all kinds of materials, including metals, inorganic minerals and organic polymers under humid conditions. 1 A complex community of microorganisms and their extracellular polysaccharides established as biofilm is a prerequisite for corrosion and/or deterioration of the underlying materials. 2, 3 This affects great-economic-value metallic structures like bridges and pipes; 70% of the corrosion in gas transmission lines are due to problems caused by microorganisms. 4,5 Metallic structures are generally protected by anti-corrosion coatings, but biofilm over these coatings can lead to blistering and adhesion loss, causing failure of the protective system. 6Filamentous fungi are regarded as the microorganisms that cause the most spoilage of paint films. 7 They are eukaryotic microorganisms that have extensive vegetative phase networks (mycelium) that release enzymes, glycoproteins and organic chelators. 8 Therefore, they are actively involved in corrosion processes because they can modify the substrates they grow on by chemical degradation and differential aeration and cracked zones. 4,9